Theoretical mechanistic study of CO catalytic oxidation by O2 on an ultra-small 13-atom bimetallic Ag7Au6 cluster - Preeyaporn Poldorn (2020)
© 2020 Elsevier B.V. We report an advanced configurational sampling method that uses density functional theory (DFT) to design a highly active catalyst for conversion of CO into less-harmful products, under ambient conditions. The reaction pathway for CO oxidation by O2 on ultra-small 13-Atom bimetallic Ag7Au6 cluster has two possible mechanisms, namely, stepwise adsorption and co-adsorption. The rate-determining step involving with CO[sbnd]O association via a co-adsorption process shows a significantly small barrier of 0.21 eV. Furthermore, microkinetic simulation results suggest that CO oxidation rates and the optimal temperature for CO oxidation exhibit both greater performances for the co-adsorption pathway, compared to that for a stepwise-adsorption mechanism. Our new proposed mechanism suggests that the bimetallic Ag7Au6 catalyst is active for CO oxidation at room temperatures. Thus, it has potential application as a highly-active catalyst for conversion of carbon monoxide into less toxic CO2.